2015
DOI: 10.5812/ircmj.18776
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Hausa Version of Multidimensional Scale of Perceived Social Support Index

Abstract: Background:Social support has been identified as one of the key factors for enhancing the quality of life after stroke. However, a scientific tool that is valid for evaluating social support among stroke survivors in Nigeria has not been developed so far.Objectives:The objective of this study was to examine the psychometric properties of the Hausa translated versions of the Multidimensional Scale of Perceived Social Support (MSPSS) and to validate it for future use in clinical research in Nigeria.Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
3
22
2
Order By: Relevance
“…Our findings support the observation reported in a study of college students and psychiatric outpatients (Clara et al, 2003) in which the correlated 3-factor model (first model), as well as the second order model with a single domain of overall perceived social support (fourth model), exhibited a satisfactory fit. In contrast to our findings, a study that examined the factor structure of the MSPSS in a sample of patients (N = 140) receiving treatment for stroke in Northern Nigeria (Mohammad et al, 2015) reported that the first-order bifactor model (second model) initially reported among elderly patients with generalized anxiety disorder (Stanley et al, 1998) had the best model fit indices (CFI = 0.955, RMSEA = 0.079).…”
Section: Pansi-positivecontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings support the observation reported in a study of college students and psychiatric outpatients (Clara et al, 2003) in which the correlated 3-factor model (first model), as well as the second order model with a single domain of overall perceived social support (fourth model), exhibited a satisfactory fit. In contrast to our findings, a study that examined the factor structure of the MSPSS in a sample of patients (N = 140) receiving treatment for stroke in Northern Nigeria (Mohammad et al, 2015) reported that the first-order bifactor model (second model) initially reported among elderly patients with generalized anxiety disorder (Stanley et al, 1998) had the best model fit indices (CFI = 0.955, RMSEA = 0.079).…”
Section: Pansi-positivecontrasting
confidence: 99%
“…tor (Mohammad et al, 2015). To the knowledge of the authors of this current study, the psychometric characteristics of the MSPSS in terms of its factor structure, reliability and validity among the Nigerian adolescent population have not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reliability analysis, the internal consistency was 0.78. 33 The internal consistency of the measure was 0.93 (a) in this study. We used sociodemographic data, knowledge, self-efficacy, anxiety, depression, and social support as independent variables and self-management as the dependent variable.…”
Section: Measurementssupporting
confidence: 50%
“…Elsewhere, the traditional Chinese 45 and Urdu (Pakistani) 46 versions of the MSPSS yielded a 1-factor structure, and both the Spanish 47 and Hausa (Nigerian) 48 translations yielded 2-factor structures. It is postulated that differences in culture influence ones' perception of the amount of social support rendered.…”
Section: Discussionmentioning
confidence: 99%